Factors in Developing Creative Industry - maskarto lucky nara rosmadi (Budapest International Research and Critics University, 2018)
This study aims to find out and analyze factors to support the development of creative industries. The research method used is a qualitative method with a descriptive approach. From the results of research conducted to get creative results because it is supported by highly reliable and high-quality human resources. The constraints used in developing the creative industry are snacks that are used to increase production and also from the banking sector.